(untitled) (MAUSAM, 1991)
The cyclone which occurred in the Bay of Bengal during November 1989 produced relatively less rainfall and the damage though intensive was confined to a relatively small area. After landfall the system weakened rapidly. Salient features of the cyclone are discus3ed and a comparative study has also been made with the cyclone of November 1984 and the results presented.